Isokinetic evaluation of the knee extensors and flexors anaerobic capacity - Tsaklis, P. (Isokinetics and Exercise Science, 2002)
This study focused on the design of an isokinetic test protocol for the evaluation of the anaerobic power-capacity of the knee extensors and flexors, and its validation using the Wingate 30'' anaerobic test. Twenty male track and field, sprint and jumping events athletes aged 17--28 years took part in the study. In the first session evaluation of lower limb anaerobic power took place. Following 48 hours their knee extensors and flexors were tested isokinetically (30 Reps at 240°/sec for 30s). The results have indicated a very high correlation coefficient r=0.927 between the values of the medium power for both tests, while the correlation coefficient between the fatigue indexes was relatively low r=0.485. Thus isokinetic testing of knee musculature could provide a valid measure of the anaerobic capacity of the knee extensors and flexors, particularly with respect to athletes who perform through the anaerobic glycolitic way. On the other hand, isokinetically-based fatigue could not be compared with the more common and is therefore not advisable as an alternative indicator to the Wingate test.